In Situ Reflectance Spectra of Glacier Facies - Allen Pope (Arctic Data Center, 2014)
Reflectance spectra (Hemispherical Directional Reflectance, HDR) were collected during two field campaigns from the full range of facies available on end-of-melt-season glaciers. In August 2010, data were collected on Midtre Lovénbreen. In August 2011, data were collected on the major western outlet of Langjökull. These two locations were chosen so as to include sampling of glaciers that had undergone different accumulation and melting histories. Additional differences were introduced by the springtime eruption of Grímsvötn, which deposited windborne ash on Langjökulls surface. All spectra were measured with an ASD FieldSpec Pro on loan from the UKs Natural Environment Research Councils Field Spectroscopy Facility (FSF).